Efektivitas Perubahan Kurikulum: Menciptakan Keseimbangan Antara Inovasi dan Konsistensi - Rabi'ah Rabi'ah (Madrasah: Jurnal Pendidikan Madrasah, 2024)
Curriculum change is one of the strategic efforts to improve the quality of education. An innovative curriculum aims to create a dynamic and relevant learning environment, which can better prepare students to face future challenges. However, this change is often faced with major challenges, especially in maintaining a balance between innovation and consistency in delivering subject matter. This study aims to identify and analyze strategies that can be used to create a balance between innovation and consistency in curriculum change. The research method is a Literature Study, the type of literature study research (Library Research) is a data collection technique using a review study of books, notes, and reports related to the problems being solved. The results of this study provide strong evidence that curriculum changes that integrate innovation with consistency can bring great benefits to the education system. The importance of support from all stakeholders, teacher readiness, and the use of relevant indicators to measure the effectiveness of curriculum changes are also emphasized. By implementing these findings, it is hoped that a more adaptive, responsive, and effective education system can be created in preparing future generations.